Stigma Masyarakat Terhadap Perempuan Berstatus Cerai Hidup di Kota Tanjungpinang - Suryana, Agi; Arieta, Siti; Wahyuni, Sri (CV Insan Kreasi Media, 2023)
The phenomenon of women with divorced status is common in Indonesia. The high divorce rate in Tanjungpinang City has an impact on the number of women who have divorced status. Women with divorced status are still attached to a number of stigmas. The strongest stigma is that women with divorced status are considered to be able to behave negatively and are followed by jokes that cover up this status, such as women who are weak and cannot be single parents, fail to take care of the household and have the potential to commit deviant behavior. This research was conducted to find out the stigma against women with divorced status. The theory used in this research is the stigma theory. There were twelve informants in this study, namely women with divorced status, families and the community of Tanjungpinang city. This type of research is qualitative and the selection of informants uses a purposive sampling technique with several predetermined criteria. The results of this study indicate that there is a social stigma against women with divorced status living in Tanjungpinang City. Stigma caused by actions that have the potential to deviate from the status of divorced women. Community stigma is inseparable from censorship and community interaction. The causes of the emergence of stigma are patriarchal culture in society, level of education, age and gender and social conditions